(untitled) (Ustozlar uchun, 2026)
Accuracy of digital dental models is a critical determinant of marginal fit, occlusal precision, and long-term success of fixed prosthetic restorations. Both the physical properties of impression materials and the optical characteristics of scanning methods play a decisive role in the fidelity of CAD/CAM-generated models.